ANALISIS PELAYANAN PUBLIK DALAM PROSES PELAKSANAAN PENERIMAAN ANGGOTA KEPOLISIAN REPUBLIK INDONESIA DI KEPOLISIAN DAERAH BENGKULU - Sakti, Budiman; Ronanda, Aditya Candra; Aprianty, Henny; Dani, Rahiman (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
This research aims to analyze public services in the process of implementing the recruitment of National Police members in the Bengkulu Regional Police area. This research uses a qualitative approach, with data collection methods through observation, interviews and documentation support. Informants in this research came from organizers, participants, and guardians of selection participants. The research results show that overall the public services provided are in accordance with service standards. In the dissemination of information, acceptance is carried out with openness, there are no measures to limit the dissemination of information. Implementation accountability also complies with existing standards and regulations. Community participation is also involved in order to increase supervision of the admission process. And there are no acts of discrimination against participants starting from the registration process to the stages of each test category. The conclusion is that public services have been implemented as well as possible in accordance with the existing standards and rules in the admission selection process.